I am Malala : the girl who stood up for education and changed the world - Yousafzai, Malala, 1997- (Little, Brown and Co., 2016)
Malala Yousafzai's describes her fight for education for girls under Taliban rule, the support she received from her parents to pursue an education, and how the Taliban retaliated against her by trying to kill her.